THE IMPACT OF ACUTE RESPIRATORY INFECTIONS ON THE MYOCARDIUM OF THE HEART IN PREMATURE CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acute respiratory infections (ARIs) remain a significant cause of morbidity and mortality in premature children due to their underdeveloped immune and cardiovascular systems. This article explores the impact of ARIs on the myocardium of the heart in preterm infants, emphasizing the pathophysiological mechanisms, clinical manifestations, and potential complications. It highlights how viral and bacterial pathogens involved in respiratory infections may contribute to myocardial inflammation, arrhythmias, and reduced cardiac output. Special attention is given to diagnostic challenges and the importance of early intervention and monitoring of cardiac function in neonatal intensive care units. Understanding the interplay between respiratory infections and cardiac health is critical for improving outcomes in this vulnerable population.